The relationship between organizational commitment and performance among Goverment-linked Corporation's (GLC) among employees at Sarawak Energy Berhad / Suzette Gilbert - Gilbert, Suzette (2018)
The objective of this study was to investigate the relationship between organizational commitment and job performance. The fundamental target of this study was to identify the relationship between organizational commitment and job performance. This study included 162 staff at Sarawak Energy Berhad, Kuching, Sarawak as the sample size of this survey. The data collection method was questionnaire survey that was distributed to all the 162 employees at SEB. Reliability test for the instrument used was done using SPSS version 20.0. The outcome demonstrates that every element of Organizational Commitment has positive and negative significant correlation with Job Performance. It is recommended that future analyst should expand the number of respondents and conduct the future research in government-linked corporations.